Twists and Turns in the Salicylate Catabolism of Aspergillus terreus, Revealing New Roles of the 3-Hydroxyanthranilate Pathway - Tiago M. Martins (American Society for Microbiology, 2021)
ABSTRACT In fungi, salicylate catabolism was believed to proceed only through the catechol branch of the 3-oxoadipate pathway, as shown, e.g., in Aspergillus nidulans. However, the observation of a transient accumulation of gentisate upon the cultivation of Aspergillus terreus in salicylate medium questions this concept. To address this, we have run a comparative analysis of the transcriptome of these two species after growth in salicylate using acetate as a control condition. The results revealed the high complexity of the salicylate metabolism in A. terreus with the concomitant positive regulation of several pathways for the catabolism of aromatic compounds. This included the unexpected joint action of two pathways—3-hydroxyanthranilate and nicotinate—possibly crucial for the catabolism of aromatics in this fungus. Importantly, the 3-hydroxyanthranilate catabolic pathway in fungi is described here for the first time, whereas new genes participating in the nicotinate metabolism are also proposed. The transcriptome analysis showed also for the two species an intimate relationship between salicylate catabolism and secondary metabolism. This study emphasizes that the central pathways for the catabolism of aromatic hydrocarbons in fungi hold many mysteries yet to be discovered. IMPORTANCE Aspergilli are versatile cell factories used in industry for the production of organic acids, enzymes, and pharmaceutical drugs. To date, bio-based production of organic acids relies on food substrates. These processes are currently being challenged to switch to renewable nonfood raw materials—a reality that should inspire the use of lignin-derived aromatic monomers. In this context, aspergilli emerge at the forefront of future bio-based approaches due to their industrial relevance and recognized prolific catabolism of aromatic compounds. Notwithstanding considerable advances in the field, there are still important knowledge gaps in the central catabolism of aromatic hydrocarbons in fungi. Here, we disclose a novel central pathway, 3-hydroxyanthranilate, defying previously established ideas on the central metabolism of the aromatic amino acid tryptophan in Ascomycota. We also observe that the catabolism of the aromatic salicylate greatly activated the secondary metabolism, furthering the significance of using lignin-derived aromatic hydrocarbons as a distinctive biomass source.